Pengaruh Harga, Brand Image, Personal Branding, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Batik: Studi Kasus Pada Batik Riziq Pekalongan - Khofifah Irnaza; Ali Imron (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to test, analyze and explain the influence of price, brand image, personal branding and service quality on decisions to purchase batik products at Batik Riziq Pekalongan partially and simultaneously. This research is a type of quantitative research. This research was conducted using a questionnaire to 100 respondents of Batik Riziq Pekalongan consumers. Sampling used non-probability sampling with purposive sampling technique. This research uses multiple linear regression analysis. The data that has been collected is processed using the SPSS version 25 program. The results obtained in the research show that partially price (X1), brand image (X2), and service quality (X4) each have an influence on purchasing decisions (Y), while partially personal branding (X3) has no effect on purchasing decisions (Y). Meanwhile, the results of simultaneous testing show that price (X1), brand image (X2), personal branding (X3) and service quality (X4) together influence the purchasing decision (Y) of batik products at Batik Riziq Pekalongan.